2016
DOI: 10.1111/ceo.12707
|View full text |Cite
|
Sign up to set email alerts
|

Blood culture bottles are superior to conventional media for vitreous culture

Abstract: Background: To compare blood culture bottles and conventional media for the vitreous culture in patients with clinically suspected infectious endophthalmitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…In the present study, both conventional culture media and blood culture bottles were used for culture of the vitreous fluid specimens, because this laboratory’s previous studies revealed that vitreous culture in blood culture bottles yielded more positive results than conventional culture media, and a combination of both improved the possibility of a positive culture. 8 , 9 The culture yield in this study was only 41.25%. This may be attributed to many factors.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In the present study, both conventional culture media and blood culture bottles were used for culture of the vitreous fluid specimens, because this laboratory’s previous studies revealed that vitreous culture in blood culture bottles yielded more positive results than conventional culture media, and a combination of both improved the possibility of a positive culture. 8 , 9 The culture yield in this study was only 41.25%. This may be attributed to many factors.…”
Section: Discussionmentioning
confidence: 54%
“… 4 , 6 , 21 This study, however, agrees with previous studies in Thailand. 5 , 8 , 9 This may be attributed to a higher incidence of ocular trauma, especially with vegetative material, in the rural areas. Post-operative endophthalmitis was the next most common and similar to other previous studies, where most of the patients developed infection after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Conventional culture methods (CM) use solid or broth media including thioglycolate. However, rates of identification increase when blood culture bottles (BCBs) are used (3,6–9).…”
Section: Introductionmentioning
confidence: 99%